Proceedings of the Mulawarman International Conference on Economics and Business (MICEB 2017) 2018
DOI: 10.2991/miceb-17.2018.37
|View full text |Cite
|
Sign up to set email alerts
|

How Does Policy on Accreditation Affect the Quality Improvement in Indonesian Hospitals

Abstract: There was a new Law in 2009 [1] about hospital that is seeking to improve the quality of health services across all Indonesian hospitals. One of specific attention is mandatory aspect of accreditation process. By using accreditation process the quality of health services will be improved through such criteria and standards for hospitals that are disclosed in other government regulations (such as the Ministry of Health Decree No: 129/Menkes/SK/II/2008). On the other hand, the quality improvement processes are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Previous studies revealed that is influenced by many factors to understand the quality nursing care. Based on local studies, there are several factors, including nursing care delivery model (Mendrofa & Sagala, 2019), accreditation (Avia & Hariyati, 2019;Sari, 2017), high workload, tasks out of the nursing roles, and the pace of nurses to finish their job (Roro Lia Chairina, Andi Sularso, Sulianti K Tobing et al, 2019).…”
Section: List Of Figuresmentioning
confidence: 99%
“…Previous studies revealed that is influenced by many factors to understand the quality nursing care. Based on local studies, there are several factors, including nursing care delivery model (Mendrofa & Sagala, 2019), accreditation (Avia & Hariyati, 2019;Sari, 2017), high workload, tasks out of the nursing roles, and the pace of nurses to finish their job (Roro Lia Chairina, Andi Sularso, Sulianti K Tobing et al, 2019).…”
Section: List Of Figuresmentioning
confidence: 99%